Effective Online Learning of Interest and Impact on Self-Directed Students in Mechanical Education - Idkhan, A Muhammad; Irfan, A. Muhammad; Putra, Iswahyudi Indra; Romadin, Achmad; Nawi, Mohd Zulfakar Mohd (East Asian Journal of Multidisciplinary Research, 2024)
The internet network greatly supports the smooth conduct of online learning. If the network is inadequate, online learning will be difficult to carry out, thus hampering the learning process and making it ineffective. The high cost of internet packages for large data quotas is also a problem faced by students when accessing services such as Zoom meetings, YouTube, and Google Meet, which require a significant amount of data. Additionally, some areas in Indonesia still have poor internet access or are difficult to connect to the network. Interest in learning is a strong desire within a person that can generate a response, enthusiasm, and motivation, stimulating the brain to command the body to take action. This stimulation leads to engagement in learning activities with the aim of gaining knowledge from the subject being studied. High learning interest among students is expected to foster self-directed learning, enhancing their creativity in seeking various learning resources that can be used as references in the online teaching and learning process, especially during the pandemic era.